Transformation of Education in Elementary Schools: The Secret Behind Teacher Professionalism and the Surge in Literacy and Numeracy! Transformation of Education in Elementary Schools The Secret Behind Teacher Professionalism and the Surge in Literacy and Numeracy! - Hullatul Luthfiyah; Mardhatillah; Oktaviani Adhi Suciptaningsih (Inovasi Sekolah Dasar: Jurnal Kajian Pengembangan Pendidikan, 2025)
This study aims to evaluate teacher professionalism and learning effectiveness at SD Negeri Sumbertaman 2, with a focus on literacy, numeracy, and parental involvement in supporting children's education. The method employed was a descriptive mini-research approach, involving questionnaires, interviews, and observations, with participants comprising 27 students, 27 parents, and several teachers. Results showed that the majority of students rated their teachers as professional in explaining material, supporting learning, and being fair. Students' literacy reached the minimum competency of 60%, while numeracy was only 26.67%. Parents provided an upbeat assessment of the teacher's communication, although they expected more specific feedback. This study recommends increasing teacher training in numeracy, implementing context-based learning methods, and strengthening parental involvement to improve overall student learning outcomes.